Unemployment insurance savings accounts in Latin America: Overview and assessment - Ana M. Ferrer; W. Craig Riddell (Institute for the Study of Labor (IZA), 2011)
The unemployment protection systems that exist in most Latin American economies are generally considered inadequate in terms of providing insurance to workers. They may also encourage stratified labor markets and impose barriers to the employee's mobility and the firm's adjustment to changing labor market conditions. In addition, some of these systems involve high administrative and monitoring costs and may create additional adverse effects that induce higher unemployment rates and longer duration of unemployment and promote informal labor markets. Recently, research effort and policy interest has turned to Unemployment Insurance Savings Accounts (UISAs) as an alternative to traditional systems of unemployment insurance. UISAs are schemes of individual mandatory savings. Therefore, they smooth income over an individual's life cycle rather than pooling unemployment risk over the total working population at a point in time. This form of unemployment insurance diminishes the moral hazard problems associated with traditional insurance methods. However, it presents problems of its own. First, it is questionable that these systems provide adequate protection against unemployment risk. Additionally, their effects on the promotion of informal labor markets and their administrative costs are yet to be determined. Finally, the effectiveness as a form of unemployment insurance depends critically upon the performance and credibility of the financial institutions managing the funds. This paper examines the experience of Latin American countries that use UISAs, with the hope of highlighting the problems of the system and identifying areas for future theoretical and empirical work. The overall effect of UISAs depends on a vast array of specific country characteristics and program parameters. The way the system is implemented, existing labor regulation, the extent of the informal economy and the scope for collusive behavior greatly influence the success of these programs. This calls for a more extensive research effort in the area.
urn:nbn:de:101:1-201104133997
Keywords: J65; J08; 330; unemployment insurance; moral hazard; severance pay; Latin America; labor markets; Arbeitslosenversicherung; Privatversicherung; Sparen; Beschäftigungseffekt; Informeller Sektor; Abfindung; Moral Hazard; Lateinamerika